(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2021)
The subject Contemporary German language 1-8 constitutes the foundation of the Bachelor study program within the module Language, literature, culture at the Department for German studies at the Faculty of Philology, University of Belgrade. Therefore it is reasonable to expect that the students would come into contact with the culture not only of the countries whose language they are learning, but of their own culture as well during their studies. Since language and culture are inseparable, the aim of this research is to investigate to which extent the intercultural contents are present within the course Contemporary German language. The research is aimed at the students’ estimation regarding the presence of cultural elements in the lessons. For the purpose of the study a questionnaire has been created. The acquired data will serve as an incentive for a refreshment of the curriculum of this course.